The Main Character's Inner Conflict in the Novel Ayah, Berjuang Sendiri Itu Capek by Adellia PD: A Psychoanalytic Perspective : - Siti Maysaroh (Raja Zulkarnain Education Foundation, 2026)
This study aims to analyze the inner conflict of the main character, Brichia, in the novel Ayah, Berjuang Sendiri Itu Capek! by Adellia P.D. (2025). This inner conflict arises due to the conflict between financial and moral responsibilities towards the family and the character’s desire to achieve her dream of becoming a doctor. This study uses a qualitative descriptive method with a literary psychology approach, specifically Sigmund Freud’s psychoanalytic theory which includes the personality structure of the id, ego, and superego as well as self-defense mechanisms. The main data source of this study is the novel Ayah, Berjuang Sendiri Itu Capek! published in 2025. Supporting data is obtained from reference books, scientific articles, and relevant research related to literary psychology. Data collection techniques are carried out through intensive reading and recording data in the form of narrative excerpts and dialogues that represent the character’s inner conflict. Data analysis is carried out by classifying data based on aspects of the id, ego, superego, and forms of self-defense mechanisms. The results of the study indicate that Brichia’s inner conflict is caused by the dominance of the id that drives the fulfillment of personal ambition, the superego that instills moral values and a sense of responsibility towards the family, and the role of the ego that tries to mediate these two drives through rational actions, such as seeking realistic educational alternatives. To reduce psychological stress, Brichia uses self-defense mechanisms, including repression, projection, and sublimation. This inner conflict contributes to the formation of Brichia’s character as an independent, tough, and principled woman.Keywords: inner conflict, Sigmund Freud’s psychoanalysis, id, ego, superego, Father, Fighting Alone Is Tiring!